Evaluación de la Cartera de Crédito de las COAC Segmento 1 de la ciudad de Loja y su impacto en la Información Financiera, periodo 2020-2022 - Amay Armijos, Jhuliana Elizabeth (2023)
The evaluation focuses on the key indicators of the credit portfolio, risk and provisions, and their impact on the financial results of three cooperatives: COAC Manuel Esteban Godoy, COAC Padre Julián Lorente y COAC de la Pequeña Empresa de Loja, the late payment was analyzed in the years 2020, 2021 and 2022 for each entity. This data determined a gradual increase in late payments in all cooperatives as the years progressed, due to the continued effects of the pandemic on the economy. The coverage of unproductive portfolio was examined through the provision in relation to bad debts, all cooperatives maintained high coverage, indicating caution in times of uncertainty, it was used an analytical approach that combines financial indicators such as ROE (Return on Equity) and ROA (Return on Properties). Similarly, the correlation analysis was used to identify possible relationships between these indicators, late payment, and provisions. The factors that influence the credit portfolio were examined, addressing aspects such as the novated, refinanced, restructured and punished portfolio. With the purpose of exploring the process of credit operation, it was applied a meticulous, structured, and well-designed interview. This allowed a deep understanding of how these complex elements affects the management of credit portfolio directly. Nonpayment is influenced by the COVID-19 pandemic, over-indebtedness and lack of liquidity. A series of strategies were proposed to address these problems and improve portfolio recovery, like the renegotiation of debts through novation, the grant of preferential loans to AAA partners and an effective segmentation of debtors to optimize collection management.